2017
DOI: 10.1016/j.vetmic.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping and conservation analysis of linear B-cell epitopes of peste des petits ruminants virus hemagglutinin protein

Abstract: Hemagglutinin protein (H), one of the two glycoproteins of peste des petits ruminants virus (PPRV), binds to its receptor on the host cell and acts as a major antigen that induces and confers highly protective immunity in the host. In order to delineate the epitopes on H protein, fine epitope mapping and conservation analysis of linear B-cell epitopes (BCEs) on PPRV H has been undertaken using biosynthetic peptides and rabbit anti-PPRV H sera. Thirteen linear BCEs were identified and their corresponding minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…As such, the low homology in H proteins among the two PPRV strains under study could possibly account for the differences in immunogenicity observed for the two PPRV VLPs. The H protein of PPRV is a 609-residue type II integral membrane glycoprotein (Yu et al, 2017). The two PPRV strains under investigation differ by a total of 43 amino acids distributed among the N-terminal cytoplasmic tail (three mutants), stalk region (three mutants), and C-terminal globular head (37 mutants) containing the receptor binding site and immune epitopes, respectively (Figure 6; Colf et al, 2007;Yu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the low homology in H proteins among the two PPRV strains under study could possibly account for the differences in immunogenicity observed for the two PPRV VLPs. The H protein of PPRV is a 609-residue type II integral membrane glycoprotein (Yu et al, 2017). The two PPRV strains under investigation differ by a total of 43 amino acids distributed among the N-terminal cytoplasmic tail (three mutants), stalk region (three mutants), and C-terminal globular head (37 mutants) containing the receptor binding site and immune epitopes, respectively (Figure 6; Colf et al, 2007;Yu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the key to achieve this goal is that entire IgG-epitomes of several target viral proteins and all type-specific BCEs in them can be revealed. Now, it is achievable since all linear BCEs present in a protein and type-specific BCEs in them has been able to be delineated using rabbit/murine pAbs using the BSP method specific for BCE mapping [35,36], which has been used in many studies of mapping BCEs on different viral protein using rabbit pAbs and BSPs [30,[48][49][50][51][52]. Our previous study has revealed three IgG-epitomes of E6, E7…”
Section: Discussionmentioning
confidence: 99%
“…Now, with the establishment of BSP methods specific for BCE mapping by BCEs mapped by rabbit pAbs to HPV58-L1 were reacted with murine pAbs to HPV58 L1-VLPs [30]. All 19 and 9/13 RR-BCEs on nucleoprotein (NP) and hemagglutinin (H) proteins of peste des petits ruminants virus (PPRV) were recognized by sera from goat with PPRV-positive, respectively [48,49]. Similarly, there was evidence that 3 of 4 RR-peptides on HPV18-E6 can be recognized by human sera to HPV18 in ELISA test [29].…”
Section: Discussionmentioning
confidence: 99%
“…For rational vaccine design or development of diagnostic tools, it is necessary to map the specific and conserved BCEs of target proteins [ 21 ]. Also, multi-epitope-based vaccines offer numerous advantages compared to the complete protein, including cost-effective production, stability under different conditions and multivalency [ 24 ]. Recently, Zhao et al [ 33 ] constructed a recombinant epitope vaccine that contains six immunodominant epitopes, and they demonstrated its capacity to induce a robust IgG specific response.…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples of a healthy rabbit and a healthy sheep with no history of CCHFV infection were used as negative controls in the western blotting assay. Escherichia coli BL21 (DE3) competent cells were used to express 16/8mer peptides fused with a truncated GST188 protein (i.e., with the initial 188 aa of GST) [ 24 ]. Goat anti-rabbit and mouse anti-goat IgG conjugated to horseradish peroxidase (HRP) were purchased from Beijing TransGen Biotech, Co., Ltd. (China).…”
Section: Methodsmentioning
confidence: 99%